European core curriculum in cariology for undergraduate dental students - Schulte, Andreas G.; Pitts, N. B.; Huysmans, M. C. D. N. J. M.; Splieth, C.; Buchalla, W. (Caries research, 2011)
As dental caries prevalence is still high in many populations and groups of both children and adults worldwide, and as caries continues to be responsible for significant health, social and economic impacts, there is an urgent need for dental students to receive a systematic education in cariology based upon current best evidence. Although European curriculum guidelines for undergraduate students have been prepared in other dental fields over the last decade, none exist for cariology. Thus the European Organisation for Caries Research (ORCA) formed a task force to work with the Association of Dental Education in Europe (ADEE) on a European Core Curriculum in Cariology. In 2010, a workshop to develop such a curriculum was organised in Berlin, Germany, with 75 participants from 24 European and 3 North-South American countries. The Curriculum was debated by five pre-identified working groups: I The Knowledge Base; II Risk Assessment, Diagnosis and Synthesis; III Decision-making and Preventive Non-surgical Therapy; IV Decision-making and Surgical Therapy; and V Evidence-based Cariology in Clinical and Public Health Practice and then finalised jointly by the group chairs. According to this Curriculum, on graduation, a dentist must be competent at applying knowledge and understanding of the biological, medical, basic and applied clinical sciences in order to recognise caries and make decisions about its prevention and management in individuals and populations. This document, which presents several major and numerous supporting competences, does not confine itself to dental caries alone, but refers also to dental erosion/non-erosive wear and other dental hard tissue disorders.
Gesehen am 27.10.2022